La prédiction de la délinquance - Loeber, Rolf; Stouthamer-Loeber, Magda (Criminologie, 1986)
The paper presents the results of a meta-analysis to analyze which predictors of delinquency in males and females are consistently evident from longitudinal studies, and how the predictors compare in their predictive efficiency. The results show that a variety of conduct problems but also conditions within the family are predictive of later delinquency in general, recidivism, or serious offenses. As a rule, composite indicators of risk factors outperformed single indicators. Data is presented on the early identification of chronic offenders. The results are critically examined in terms of error rates, and in terms of future directions for research.